Global governance for pandemic prevention and the wildlife trade. Issue 4 (April 2023) - Gallo-Cajiao, Eduardo; Lieberman, Susan; Dolšak, Nives; Prakash, Aseem; Labonté, Ronald; Biggs, Duan; Franklin, Christine; Morrison, Tiffany H; Viens, A M; Fuller, Richard A; Aguiar, Raphael; Fidelman, Pedro; et al.
Summary: Although ideas about preventive actions for pandemics have been advanced during the COVID-19 crisis, there has been little consideration for how they can be operationalised through governance structures within the context of the wildlife trade for human consumption. To date, pandemic governance has mostly focused on outbreak surveillance, containment, and response rather than on avoiding zoonotic spillovers in the first place. However, given the acceleration of globalisation, a paradigm shift towards prevention of zoonotic spillovers is warranted as containment of outbreaks becomes unfeasible. Here, we consider the current institutional landscape for pandemic prevention in light of ongoing negotiations of a so-called pandemic treaty and how prevention of zoonotic spillovers from the wildlife trade for human consumption could be incorporated. We argue that such an institutional arrangement should be explicit about zoonotic spillover prevention and focus on improving coordination across four policy domains, namely public health, biodiversity conservation, food security, and trade. We posit that this pandemic treaty should include four interacting goals in relation to prevention of zoonotic spillovers from the wildlife trade for human consumption: risk understanding, risk assessment, risk reduction, and enabling funding. Despite the need to keep political attention on addressing the current pandemic, society cannot afford to miss the opportunity of the current crisis to encourage institution building for preventing future pandemics.